Pengaruh Sistem Pengendalian Intern Pemerintah Terhadap Efektivitas Pengelolaan Keuangan Pada Badan Pengelola Keuangan dan Aset Daerah Kabupaten Musi Banyuasin - Jumania Septariani; Rano Asoka (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2020)
This study aims to determine the effect of the government's internal control system on the effectiveness of the regional financial management of the Musi Banyuasin Regency Government. The types and sources of data used by the author in this study are primary and secondary data. In this study, the author used quantitative analysis techniques. The results of the study stated that the government internal control system in the Government of Musi Banyuasin Regency was adequate, this was supported by research indicators namely elements of the government's internal control system consisting of the control environment, risk assessment, control activities, information and communication and monitoring. The effectiveness of regional financial management in the Musi Banyuasin District Government is very effective, this is supported by research indicators, namely the objectives of regional financial management consisting of responsibilities, being able to fulfill financial obligations, honesty, efficiency and effectiveness and effective and controlling activities. There is an influence of the government's internal control system on the effectiveness of regional financial management in the Musi Banyuasin District Government.